Religion and Place
XIV, 222 p.
Keywords: This unique collection highlights the importance of landscape, politics and piety to our understandings of religion and place. The geographies of religion have developed rapidly in the last couple of decades and this book provides both a conceptual framing of the key issues and debates involved, and rich illustrations through empirical case studies. The chapters span the discipline of human geography and cover contexts as diverse as veiling in Turkey, religious landscapes in rural Peru, and refugees and faith in South Africa. A number of prominent scholars and emerging researchers examine topical themes in each engaging chapter with significant foci being: religious transnationalism and religious landscapes; gendering of religious identities and contexts; fashion, faith and the body; identity, resistance and belief; immigrant identities, citizenship and spaces of belief; alternative spiritualities and places of retreat and enchantment. Together they make a series of important contributions that illuminate the central role of geography to the meaning and implications of lived religion, public piety and religious embodiment. As such, this collection will be of much interest to researchers and students working on topics relating to religion and place, including human geographers, sociologists, religious studies and religious education scholars.